2004
DOI: 10.1081/jdi-120038501
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Patients on Maintenance Hemodialysis and Effect of Chronic Hepatitis C Virus Infection

Abstract: However the mean BMD values for all three sites in the 76 HD patients were low HCV infection may not be a risk factor for low BMD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
2
13
0
2
Order By: Relevance
“…In this bone DXA densitometry-based study, we detected that osteoporosis was common in dialysis patients, observed in 23% of cases. Indeed, literature data showed that the prevalence of osteoporosis varied from 4 to 47% at the lumbar spine and from 10 to 64% at the femoral site [7][8][9][10][11][12][13][14][15]. Moreover, Avramovski et al [16] demonstrated that the progression of bone mass loss was significantly greater in chronic hemodialysis patients than in general population patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this bone DXA densitometry-based study, we detected that osteoporosis was common in dialysis patients, observed in 23% of cases. Indeed, literature data showed that the prevalence of osteoporosis varied from 4 to 47% at the lumbar spine and from 10 to 64% at the femoral site [7][8][9][10][11][12][13][14][15]. Moreover, Avramovski et al [16] demonstrated that the progression of bone mass loss was significantly greater in chronic hemodialysis patients than in general population patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of musculoskeletal problems increases with time on dialysis [14]. In addition to this, malnutrition may also frequently affect the health status of the dialysis patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…3 In our study, because patients aged beyond 60 years was an exclusion criterion, we could not compare our results with those of Wolfe' s group. 27 In order to remove this confounding factor we paired the 2 groups according to length of therapy. Corroborating with our results are those of Yuceturk' s 23 which could reflect the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of musculoskeletal disturbances due to multifactorial causes rises with time on dialysis. 27 In order to remove this confounding factor we paired the 2 groups according to length of therapy. Other factors, such as the index of dialysis adequacy (Kt/V) and the body mass index were evaluated.…”
Section: Discussionmentioning
confidence: 99%